STUDI PENERAPAN BUKU AJAR IPA TERPADU TEMA GERAK DALAM MODEL PEMBELAJARAN KONTEKSTUAL ADAPTIF PADA SISWA KELAS VIII SMPN 8 PADANG - nurul fajra; Asrizal Asrizal; Zulhendri Kamus (Universitas Negeri Padang, 2018)
Integration of science teaching material in Junior High School is required in the 2013 curriculum. The integration of teaching material includes Physics, Chemistry, and Biology as sub disciplinary of science. Integration in science can improve competence of students. However, the real conditions which were found in school show that the integrated science teaching wasn’t suitable with the expected conditions. The solution of this problem was to apply the integrated science textbook on motion theme in adaptive contextual teaching model. The purpose of the research was to determine the effect of the application of integrated science textbook of motion theme in adaptive contextual teaching model toward the competences grade VIII students in SMPN 8 Padang. The type of research which conducted was quasi experiment research with one group pretest-posttest design. The research population was all students of grade VIII in SMPN 8 Padang that registered in 2017/2018 academic year. The samples in this research were grade VIII C which obtained by using the purposive sampling technique. The research instrument for knowledge competence was multiple-choice written test, attitude competency was observation sheet and skill competency was performance assessment test. Data analysis techniques in this research were descriptive statistics analysis, simple linear regression test, product moment correlation test, comparison test and determination coefficient. The result of this research shows that the application of integrated science textbook of motion theme in adaptive contextual teaching model has given significant effect on the three competences of grade VIII students including knowledge, attitude and skills at SMPN 8 Padang at 95% confidence level.